2003
DOI: 10.1038/nature01378
|View full text |Cite
|
Sign up to set email alerts
|

Structure and catalytic mechanism of the human histone methyltransferase SET7/9

Abstract: Article:Xiao, B., Jing, C., Wilson, J.R. et al. (7 more authors) (2003) Structure and catalytic mechanism of the human histone methyltransferase SET7/9. Nature, 421 (6923). pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
429
2
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 347 publications
(460 citation statements)
references
References 20 publications
(26 reference statements)
26
429
2
3
Order By: Relevance
“…Currently known structures of SET proteins include the crystal structures of two SUV family proteins, Neurospora crassa DIM-5 [23,27] (Figure 1a) and Schizosaccharomyces pombe Clr4 [28] (Figure 1b); six human SET7/9 structures in various configurations [29][30][31][32][33][34] (Figure 1c); two human SET8 (or Pr-SET7) structures [35,36] (Figure 1d); an NMR structure of a viral protein that contains only the SET domain (vSET) [37]; and a nonhistone Rubisco MTase [38,39]. These structures revealed that the SET domain forms a novel β-fold with a series of curved β-strands forming several small sheets, packed together with post-SET, pre-SET, or an additional domain (i-SET) inserted into SET domain.…”
Section: Structures Of Set Domain Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently known structures of SET proteins include the crystal structures of two SUV family proteins, Neurospora crassa DIM-5 [23,27] (Figure 1a) and Schizosaccharomyces pombe Clr4 [28] (Figure 1b); six human SET7/9 structures in various configurations [29][30][31][32][33][34] (Figure 1c); two human SET8 (or Pr-SET7) structures [35,36] (Figure 1d); an NMR structure of a viral protein that contains only the SET domain (vSET) [37]; and a nonhistone Rubisco MTase [38,39]. These structures revealed that the SET domain forms a novel β-fold with a series of curved β-strands forming several small sheets, packed together with post-SET, pre-SET, or an additional domain (i-SET) inserted into SET domain.…”
Section: Structures Of Set Domain Proteinsmentioning
confidence: 99%
“…Comparison of the structure of DIM-5 [27] with that of SET7/9 [32][33][34], and SET8 [35,36], two SET proteins that do not have a cysteine-rich post-SET domain, reveals a remarkable example of convergent evolution. In particular, like DIM-5, these two enzymes rely on residues C-terminal to the SET domain for the formation of a lysine channel, but do so by packing an α-helix, rather than a metal center, onto the active site (Figures 1c-d).…”
Section: Dim-5: the Post-set Zinc-binding Is Essential For Activitymentioning
confidence: 99%
See 3 more Smart Citations